The Impact of PAI Curriculum Development on the Quality of Memorization and Morality of Students at the Cahaya Qur'an Tahfizh House - Rizky Fika Mulia; Nailish Shofa Hidayah; Ma’mun Hanif; Nur Kholis (Hikamatzu | Journal of Multidisciplinary, 2025)
This study aims to analyze the impact to the development of the Islam Religious Education (IRE) curriculum on the quality of memorization and character building of students at Rumah Tahfizh Cahaya Qur’an Batang. The study uses a descriptive qualitative approach with data collection techniques through observation and documentation. The focus of the study was directed at the integration of PAI values and tahfizh activities in the learning process. The results showed that the PAI curriculum at Rumah Tahfizh wa integrative, in which tahfizh activities not only empasized memorization skills but also included understanding the meaning of verses and applying Islamic values. The currilum has a positive impact on the quality of students memorization, as indicated by improvements in reading accuracy, tajwid and discipline in muraja’ah. In addition, currilum development also strengthens the formation of students character through the habit of being polite to theachers, friends and parents. Teachers play a role as uswah hasanah in instilling Qur’anic values that are reflested in the students behavior. Thus, the development of the PAI curriculum at Rumah Tahfizh Cahaya Qur’an Batang has succeeded in creating a balance between cognitive abilities and spiritual character building, which is an important foundation in producing a Qur’anic generation with good character